Training of the Making of Jawawut Diamonds and Its Packaging in Kabupaten Kepulauan Selayar: Pelatihan Pembuatan Wajik Jawawut Beserta Pengemasannya Di Kabupaten Kepulauan Selayar - Husnaeni Husnaeni; Rustam Rustam; Djalil Djalil; Makkatenni Makkatenni; Ranak Lince; Kusmaladewi Kusmaladewi (Mattawang: Jurnal Pengabdian Masyarakat, 2022)
The training on making diamonds from raw materials of Jawawut is based on the abundant production of Jawawut in this area and is used as bird feed. A small portion is traditionally processed as a snack that cannot last long. This training aims to provide knowledge, understanding and skills to the people of the Selayar Islands to process Jawawut raw materials become diamond-jawawut that last a long time so that they become people's food and can support the community's economy. This training was carried out for 3 (three) consecutive months, starting from June – August 2020, the participants of this training were 22 people, consisting of the Village Head, and staff, PKK members, entrepreneurs in the Selayar Islands Regency. Participants are very enthusiastic about participating in the training, the results obtained by participants have understood, mastered and skilled in processing millet raw materials into diamonds that can last a long time as a source of additional income, can also be consumed by the local community and used as gifts for tourists both locally and abroad. Abstrak Pelatihan pembuatan wajik dari bahan baku jawawut dilandasi oleh produksi jawawut di daerah ini melimpah dan dimanfaatkan sebagai pakan burung, Sebagian kecil diolah secara tradisonal sebagai penganan yang tidak dapat bertahan lama. Olehnya itu pelatihan ini bertujuan untuk memberi pengetahuan, pemahaman dan keterampilan kepada masyarakat kepulauan selayar mengolah bahan baku jawawut menjadi wajik-jawawut yang bertahan lama sehingga menjadi bahan pangan masyarakat dan dapat menjadi penopang perekonomian masyarakat. Pelatihan ini dilaksanakan selama 3 (tiga) bulan berturut-turut, dimulai Juni – Agustus 2020, peserta pelatihan ini sebanyak 22 orang, yang terdiri dari Kepala Desa, dan staf, anggota PKK, pengusaha di Kabupaten Kepulauan Selayar. Peserta sangat antusias mengikuti pelatihan, hasil yang diperoleh peserta telah memahami, menguasai serta terampil mengolah bahan baku jawawut menjadi wajik yang dapat bertahan lama sebagai sumber penghasilan tambahan, juga dapat dikomsumsi oleh masyarakat setempat dan dijadikan oleh-oleh bagi wisatawan baik lokal maupun manca negara.